2013
DOI: 10.1016/j.yexmp.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of the microglial protein DOCK2 reduces amyloid burden in a mouse model of Alzheimer's disease

Abstract: Alzheimer’s disease (AD) neuropathology is characterized by innate immune activation primarily through prostaglandin E2 (PGE2) signaling. Dedicator of cytokinesis 2 (DOCK2) is a guanyl nucleotide exchange factor expressed exclusively in microglia in the brain and is regulated by PGE2 receptor EP2. DOCK2 modulates microglia cytokine secretion, phagocytosis, and paracrine neurotoxicity. EP2 ablation in experimental AD results in reduced oxidative damage and amyloid beta (Aβ) burden. This discovery led us to hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…Interestingly, the EP2 receptor mediates neuroprotection in rat pure neuronal cultures treated with NMDA through a PKA-dependent pathway [16], whereas EP2 activation exacerbates NMDA receptor-mediated neurotoxicity in rat cortical cultures with glia present through a cAMP-but not PKA-dependent pathway, suggesting the involvement of Epac in EP2-regulated neurotoxicity [124]. In addition, the EP2-regulated protein dedicator of cytokinesis 2 (DOCK2), another family member of GEFs, contributes to Aβ plaque burden via regulation of microglial innate immune function [125]. Taken together, the net effect of EP2 receptor activation might be determined by a yin and yang balance of the receptor in neurons and glia, and possibly by the cytoplasmic cAMP level, which is spatiotemporally regulated by the receptor to favor either PKA or Epac pathway (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the EP2 receptor mediates neuroprotection in rat pure neuronal cultures treated with NMDA through a PKA-dependent pathway [16], whereas EP2 activation exacerbates NMDA receptor-mediated neurotoxicity in rat cortical cultures with glia present through a cAMP-but not PKA-dependent pathway, suggesting the involvement of Epac in EP2-regulated neurotoxicity [124]. In addition, the EP2-regulated protein dedicator of cytokinesis 2 (DOCK2), another family member of GEFs, contributes to Aβ plaque burden via regulation of microglial innate immune function [125]. Taken together, the net effect of EP2 receptor activation might be determined by a yin and yang balance of the receptor in neurons and glia, and possibly by the cytoplasmic cAMP level, which is spatiotemporally regulated by the receptor to favor either PKA or Epac pathway (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…DOCK2 expression in mouse brain is restricted to microglia, and it is regulated by EP2. Therefore, DOCK2 may be a better therapeutic target (Cimino et al, ; Cimino et al, ). In fact, DOCK2 is co‐localized exclusively with established microglial markers tomato lectin and CD68 (Cimino et al, ).…”
Section: Dock2 In Disease Developmentmentioning
confidence: 99%
“…In brain, Dock2 is expressed exclusively in microglia and is implicated in neuroinflammation of AD pathology 19 , 20 . It has been shown that the number of Dock2-expressing microglia is abnormally increased in brains of AD patients 19 .…”
Section: Function Of Dock Protein Family In Nervous System and Its Rementioning
confidence: 99%
“…The expression of Dock2 is positively regulated by prostaglandin E2 receptors, which mediate inflammatory, neurotoxic, and amyloidogenic effects induced by the increased secretion of microglial prostaglandins during AD pathogenesis 19 . Importantly, Dock2 deficiency significantly reduces the area and size of β-amyloid (Aβ) plaque in cerebral cortex and hippocampus of a mouse model of AD 20 . Thus, Dock2 may be a key molecule that contributes to the innate immune activation and Aβ plaque burden in AD.…”
Section: Function Of Dock Protein Family In Nervous System and Its Rementioning
confidence: 99%